Bantuan Sosial Masa Pandemi Covid-19 Untuk Komunitas Sedekah Depok (KSD) GDC–Kalimulya - Dyah Utami Dewi; Hafizah Rifiyanti (Jurnal Pengabdian Teratai, 2020)
The coronavirus (COVID-19) pandemic has led to sweeping changes and disruptions in nearly every aspect of daily life. Covid-19 outbreak has a big economic impact changes, particularly from the middle to lower class society, because the economy is in decline and there are also many layoffs for employees in companies/factories. Many street vendors cannot sell normally due to the coronavirus as well., traditional motorcycle drivers, online motorcycle, taxi services cannot operate as usual due to PSBB regulations and decreased service orders due to social distancing. Many people still do not comply with government restrictions because they are forced to do so to meet their daily needs. Due to the above mentioned facts and in addition to boosting social connection and empathizing with others, some lecturers from IBI K57 worked together with KSD (Komunitas Sedakah Depok) GDC have shared breakfast packages to people in need such as garbage men, ojek drivers, scavengers, etc. This social activity The implementation of this social activity is carried out by prioritizing Covid-19 health procedures and protocols. The authors hope that this activity can be an inspiration for colleagues, students, and all communities that the awareness to share with others is the responsibility of all of us.